What About Promotores? Promotores' Psychosocial Determinants That Influenced the Delivery of a Cervical Cancer Education Intervention to Hispanics - St. John, Julie; Reininger, Belinda; Balcazar, Hector; Valerio-Shewmaker, Melissa A.; Beaudoin, Christopher E. (Frontiers in Public Health, 2021)
This study tested whether a cancer education intervention affected promotores' self-efficacy to deliver an intervention to Hispanics and which psychosocial determinants of promotores influenced the number of Hispanic residents reached by promotores in the subsequent education intervention. A quasi-experimental, pre/post-design with a treatment group (no control) assessed differences for promotores (n = 136) before and after exposure to the cancer education intervention. The design also included a cross-sectional evaluation of the number of residents promotores reached with the educational intervention. After being trained, the promotores delivered the intervention to Hispanic residents (n = 1,469). Paired t-tests demonstrated increases in promotores' self-efficacy from pre- to post-intervention. Regression models assessed associations between the numbers of residents reached and select psychosocial determinants of promotores. Age and promotores' years of experience influenced their delivery of a cervical cancer education intervention to Hispanics, but not their delivery of breast or colorectal cancer education interventions. This is the first study to examine which psychosocial determinants influence promotores delivery of cancer education interventions. The outcomes potentially have implications for CHW interventions and training by examining this potential connection between CHWs' psychosocial determinants and intervention outcomes.